Racial disparity in oncologic and quality‐of‐life outcomes in patients with locally advanced head and neck squamous cell carcinomas enrolled in a randomized phase 2 trial. Issue 13 (18th April 2018) - Guerriero, Margaret K.; Redman, Mary W.; Baker, Kelsey K.; Martins, Renato G.; Eaton, Keith; Chow, Laura Q.; Santana‐Davila, Rafael; Baik, Christina; Goulart, Bernardo H.; Lee, Sylvia; Rodriguez, Cristina P.
Abstract : BACKGROUND: To better understand patient‐reported quality of life (PRQOL) for patients with head and neck cancer, PRQOL scores were collected in a clinical trial. METHODS: Patients were randomized to arm A (70 Gy of radiation with cisplatin) or arm B (70 Gy of radiation with cisplatin plus erlotinib at 150 mg daily). PRQOL scores were measured on days –7 (arm B only), 0, 30, and 180 with the University of Washington Quality of Life Questionnaire. Associations with clinical factors and outcomes were explored with linear mixed, logistic, and Cox regression models. RESULTS: One hundred eighty‐nine patients (97 in arm A and 92 in arm B) consented to PRQOL collection. Patients were balanced apart from more females in arm A (20 [21%] vs 8 [9%]; P  = .02). There were 17 black patients (18%) in arm A and 12 (13%) in arm B ( P  = .39). There was no change in the mean scores in arm B from day –7 to day 0 ( P  = .36). Scores were lower in both arms at day 30 ( P for both < .0001), with no difference by arm ( P  = .10). Scores on day 180 remained lower for arm A (–6.79; 95% confidence interval [CI], –12.6 to –1.0; P  = .02). In arm B, this difference was not significant, and this suggested that the scores had returned to the baseline by day 180 ( P  = .73). After adjustments for potential confounders, black race was an independent predictor for inferior scores (–11.4; 95% CI, –16.84 to –5.94; P  < .0001), complete response rates (odds ratio, 0.34; 95% CI, 0.12‐0.91; P  = .03), and overall survival (hazard ratio, 3.71; 95% CI, 1.63‐8.47; P  < .01). CONCLUSIONS: PRQOL scores predictably worsened during and improved after chemoradiation. Black patients had inferior PRQOL and overall survival. Cancer 2018;124:2841‐2849 . © 2018 American Cancer Society Abstract : Patient‐reported quality of life outcome scores worsen during and improve after chemoradiation for head and neck cancer. Black patients have inferior patient‐reported quality of life and overall survival.